Mutations in CIB2 calcium and integrin‐binding protein disrupt auditory hair cell calcium homeostasis in Usher syndrome type 1J and non‐syndromic deafness DFNB48. (19th April 2013) - Jan, A
Abstract : Alterations of the CIB2 calcium‐ and integrin‐binding protein cause Usher syndrome type 1J and non‐syndromic deafness DFNB48 Riazuddin et al. (2012) Nature Genetics 44(11):1265–1271